Răspuns :
[tex] ...\;=\;\frac{1}{2}+ \frac{7}{2}- \frac{5}{11}- \frac{9}{11}= \frac{8}{2}- \frac{14}{11}=4-1\frac{3}{11}=3\frac{3}{11} [/tex]
1/2 - 5/11 + 7/2 - 9/11= 11/22 - 10/22 + 77/22 - 18/22 = 60/22 =30/11=
= 2 intregi si 8/11 = 2,(72)
→ cmmmc al numerelor ( 2,11) = 2×11=22
→ aducem fractiile la acelasi numitor (22)→ amplificandu-le cu 11, respectiv cu 2
= 2 intregi si 8/11 = 2,(72)
→ cmmmc al numerelor ( 2,11) = 2×11=22
→ aducem fractiile la acelasi numitor (22)→ amplificandu-le cu 11, respectiv cu 2